International environmental law cases : graphic reports, visual research on innovative narrative forms in journalism - Carolin Eitel and Marina Friedrich and Asuka Grün and Maria Ignacia Vollenweider and Susanna Rivas and Magdalena Kaszuba and Joanna Sivagnanam and Hannah Brinkmann (Unabhängiges Institut für Umweltfragen, 2017)
Court cases are often considered by non-lawyers to be boring and only complicated, although behind the scenes wi often discover compelling stories of human suffering and tragedy. This is especialy true for cases dealing with environmental issues since nature and its resources are exploited and destroyed wordwide thousends of times each day. Illustrations can help to make human suffering recognizable and visible, and can help readers feel connected to the characters in the story. In a unique project of the Independent Institut for Environmental Issues (UfU) e.V. a group of students of the Department of Design and Illustration of the Hamburg University of Applied Sciences has illustrated the stories behind such legal conflicts in graphic reports.
Keywords: Illustration; Graphic Report; Environment; Law Cases